Analisis Keterlambatan Penerbitan PKKA Terhadap Pembuatan Warta Kedatangan MV. MANZANILO di Balikpapan Coal Terminal - Siringoringo, Cristian Jeferson (Jurnal Cakrawala Bahari, 2025)
The Issuance of Foreign Ship Agency Approval (PKKA) is one of the essential documents in the process of a ship’s arrival at the port, as it serves as the legal basis for agents in carrying out services for foreign vessels. However, in practice, delays in the issuance of PKKA often occur, which affects other administrative processes, including the preparation of the ship arrival notice. This study aims to analyze the factors causing delays in PKKA issuance and their impact on the preparation of the arrival notice in the case of MV. Manzanilo at the Balikpapan Coal Terminal.The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and document studies. The data were analyzed by comparing the standard procedures for PKKA issuance with the practices occurring in the field. The results of the study show that delays in PKKA issuance are caused by incomplete or mismatched documents, limited coordination between agents and relevant authorities, as well as technical issues in the online application system.The impact of these delays is the obstruction of the preparation of the arrival notice, which in turn can disrupt the accuracy of ship service schedules and reduce the operational efficiency of the terminal. The conclusion of this study is that the effectiveness of the PKKA issuance process significantly influences the smoothness of ship arrival administration. Therefore, improvements in inter-agency coordination, optimization of digital systems, and enforcement of administrative discipline by agents are required to minimize delays in the future.